Verification of Energy Efficiency as a Function of the Control Mode of a Residential Heating System, Modelled in a MATLAB SIMULINK Environment - Páger, Szabolcs; Géczi, Gábor; Földi, László (Journal of Central European Green Innovation, 2023)
Efficient control of the heating system in residential buildings is of outstanding importance for energy efficiency, comfort, and emissions reduction. The use of mathematical modelling and simulation allows for the investigation and optimization of various heating control modes. During the study, we developed mathematical models to describe different control modes of the heating system in residential buildings. The most commonly used modes were constant setpoint control, variable setpoint control, weather-compensation control, and PID control. Among these, we compared the constant setpoint On/Off thermostat control with the variable setpoint control based on normal and reduced temperature time programs. Based on the models, we analysed the effectiveness and energy-saving potential of these two different control modes. The simulations were conducted using meteorological measurement data. The results showed that the variable setpoint control leads to 8,4% energy saving with minimal or negligible decrease in comfort, thus ensuring lower emissions. It can be concluded that through mathematical modelling and simulation, it is possible to conduct detailed examinations and comparisons of the heating system control modes in residential buildings. Based on the findings, designers and engineers can develop more efficient and sustainable heating solutions for residential buildings.